Agrarian and commercial change in the Southeastern Black Sea region :|production, ecology, and institutions (1850s-1910s) - Mahmuzlu, Ekin. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2019., 2019)
This dissertation examines the changes in local agricultural production, when the local market in the Southeastern Black Sea region was being integrated into global markets from the mid-1850s to 1910s. It first examines the structure of agricultural production and commerce by deconstructing each step for every major crop and then captures agrarian and commercial changes at the micro-level. Benefitting from recent developments in economic history - institutional economics and ecological economics - the thesis analyses the causality behind the agrarian and commercial change. The key finding is that although the emergence of capitalism and global markets triggered a series of agrarian and commercial changes at the global level, economic conditions, especially transportation, transaction, capital, and information costs determined the direction and limits of these agrarian and commercial changes in local agriculture and commerce. The dissertation argues that the amplitude and direction of agrarian change were determined by changes in commercial and financial institutions, innovation in transportation and information technologies, and emergence of the agro-industries under the constraint of ecological and climatic conditions. There had been two major agrarian and commercial change periods. In the first period, the longdistance agrarian market formed mostly thanks to innovations in transportation, information technologies lead to agrarian change, especially in tobacco and haricot during mid-1850s-1860s. In the second period, these markets were transformed especially thanks to institutional changes in financial institutions and emergence of agro-industries, which triggered agrarian change in tobacco, hazelnut and grains (1890s-1910).
Keywords: Agriculture -- Economic aspects -- Turkey.; Institutional economics -- History.; Economic history -- Turkey.; Agriculture -- Turkey.